Habsburgs going global. The Austro-Hungarian Concession in Tientsin/Tianjin in China (1901-1917) - Falser, Michael (Veröffentlichungen zur Kunstgeschichte, 2022)
Concessions were strictly delimited enclaves within key trading cities in China, ceded to and governed by foreign powers after 'unequal treaties' resulting from military campaigns. Within the international concession of Tientsin (today's Tianjin), a city to the south-east of Beijing, nine nations were present (1860-1946), but the Austro-Hungarian concession (1901-17) fell into oblivion. Filling this scientific gap is the overall goal of this book: its urban and architectural history will be contextualised here for the first time, making use of hitherto unknown archival material
Keywords: Austria -- Foreign relations -- China; Autriche - Relations extérieures - Chine; Austria; China; China - Tianjin; Städtebau; Stadtentwicklung; Geschichte 1901-1917; Außenhandel; Konzession; Tientsin; Österreich-Ungarn